2023
DOI: 10.3389/fmicb.2023.1315402
|View full text |Cite
|
Sign up to set email alerts
|

Moringa oleifera leaf alleviates functional constipation via regulating the gut microbiota and the enteric nervous system in mice

Xiaoyu Gao,
Weiqian Yang,
Sijin Li
et al.

Abstract: Moringa oleifera Lam. leaf is not only a new food resource in China, but also a traditional medicinal plant. It is commonly used in the folk to alleviate constipation, but its laxative mechanism is not fully understood. Hence we investigated it in loperamide-induced functional constipation (FC) mice. The results showed that MOAE significantly regulated not only gastrointestinal hormones and neurotransmitters in serum but also important gastrointestinal motility factors in the enteric nervous system (ENS)-inter… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(1 citation statement)
references
References 84 publications
(106 reference statements)
0
1
0
Order By: Relevance
“…We also found that probiotic treatment reduced the abundance of Ruminococcus , a constipation-associated bacterium. 48 Whether the other bacteria that differed between the two groups in this study significantly affected gastrointestinal symptoms or immune function has yet to be elucidated. In summation, L. plantarum 24-7 intervention has demonstrated the capacity to modulate the diversity and composition of gut microbiota in post-surgical patients, potentially underpinning the observed reduction in gastrointestinal symptoms within the probiotic group.…”
Section: Discussionmentioning
confidence: 90%
“…We also found that probiotic treatment reduced the abundance of Ruminococcus , a constipation-associated bacterium. 48 Whether the other bacteria that differed between the two groups in this study significantly affected gastrointestinal symptoms or immune function has yet to be elucidated. In summation, L. plantarum 24-7 intervention has demonstrated the capacity to modulate the diversity and composition of gut microbiota in post-surgical patients, potentially underpinning the observed reduction in gastrointestinal symptoms within the probiotic group.…”
Section: Discussionmentioning
confidence: 90%